Concentration, distribution, source apportionment, and risk assessment of surrounding soil PAHs in industrial and rural areas: A comparative study. (June 2021) - Xu, Zeyu; Wang, Chunhui; Li, Huanxuan; Xu, Shaodan; Du, Jia; Chen, Yujie; Ma, Chao; Tang, Junhong
Highlights: Levels of soil PAH in industrial area are higher than those from rural area. In industrial area, the levels of ∑16 PAHs in partial soils remain exceedingly high. Dermal contact was confirmed as the most influential exposure route. Adults might face higher potential health risk than children. Abstract: Polycyclic aromatic hydrocarbons (PAHs) are one of the important environmental pollutants that are mainly originated from industrial activities, vehicle emissions, biomass combustion, etc. Nowadays, the surrounding environment of the abandoned industrial area may still have potential health effects on the population, but current researches have paid less attention to this issue. Therefore, we report a comparative investigation focusing on the concentration, distribution, source identification, and risk assessment of PAHs in soils from surrounding areas of an abandoned industrial district and an ecological village in Zhejiang Province, China. Our findings are as follows: the levels of ∑16 PAHs ranged from 150.2 to 83096 ng·g −1 with an average concentration of 7680.4 ng·g −1 in industrial area, whereas 49.4 to 778.2 ng·g −1 with an average concentration of 213.5 ng·g −1 in rural area. Although high molecular weight PAHs were both dominant contaminants in study areas, the composition profiles of 16 priority PAHs in soils from the two sampling sites had large differences. Source identification analysis verified that fossil fuel burning and vehicle emissions were the main sources of PAHs in industrial area, while the primary sources were biomass burning and vehicle emission in rural area. The incremental lifetime cancer risk results demonstrated that dermal contact was the most influential factor for all groups, and adults might face higher potential health risk than children in both industrial and rural areas. Moreover, the overall ecological risk of soil PAH pollution was low in rural area, but some individual samples were still high in the abandoned industrial area. Our research is of great significance for the management of the surrounding environment of abandoned industrial areas.